EFEKTIFITAS PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS MODEL PROBLEM BASED INSTRUCTION TERINTEGRASI PENDIDIKAN KARAKTER UNTUK SISWA SEKOLAH DASAR - Estuhono Estuhono (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
This research was conducted based on the development of learning tools that encourage students’ creativity and skills in solving problems and motivating students to more active in the learning process. Besides that, it needed to develop students’ character values in the learning process. The development of learning tools based on integrated character education through a problem-based learning model can give solutions to this problem. The purpose of this research is to development of science learning tools for force materials based on integrated character education problem-based learning (PBI) model. This research is R & D and uses the plomp model. The Plomp model consists of the preliminary, prototyping phase, and assessment phase. The initial research phase needs analysis and contexts, literature review, and development design theory. The result of practical test based on teacher demonstrated that the score was 92.5% with the actual type. The result of students by using science learning tools shown that the cognitive category was 66%, assessment of affective nature was 72%, and the assessment of psychomotor was 95%. Based on the three types above, the average of students’ outcomes was 77.6% with the current category.